2009
DOI: 10.1027/0044-3409.217.4.197
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Impact on Victims of Traditional Bullying and Cyberbullying

Abstract: We examine the emotional impact caused to victims of bullying in its traditional form, both directly and indirectly, as well as bullying inflicted by use of new technologies such as mobile phones and the Internet. A sample of 1,671 adolescents and young people responded to a questionnaire which asked if they had been victims of various forms of bullying, as well as the emotions this caused. The results show that although traditional bullying affected significantly more young people than cyberbullying, the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
157
2
22

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(198 citation statements)
references
References 14 publications
(22 reference statements)
17
157
2
22
Order By: Relevance
“…In our sample, we found that the largest percentage of victims and aggressors were women, which is consistent with the frequencies found by Kowalski and Limber (2007) and Ortega, Elipe, Mora-Mérchan, et al (2009). However, the aggressors from our study report that the victims were generally boys, whereas girls individually and victims report that the most common perpetrators were mixed groups followed by boys individually (Li, 2008).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our sample, we found that the largest percentage of victims and aggressors were women, which is consistent with the frequencies found by Kowalski and Limber (2007) and Ortega, Elipe, Mora-Mérchan, et al (2009). However, the aggressors from our study report that the victims were generally boys, whereas girls individually and victims report that the most common perpetrators were mixed groups followed by boys individually (Li, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Indirect types of aggression are more frequent in cyberbullying, where girls outnumber boys (Kowalski & Limber, 2007). Victims' rates are also higher for girls Ortega, Elipe, Mora-Mérchan, Calmaestra, & Vega, 2009). …”
Section: From Bullying To Cyberbullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results are potentially useful for guiding resource allocation for anti-bullying programs [2], [6], [12]. Specifically, the findings suggest that such programs need to target both boys and girls across all varieties of victimization, focusing not just the victimization that can be seen and heard, but also the behaviors taking place behind closed doors and off school grounds [2], [22]- [24].…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…[11], проведенном среди испанских подростков, обнаружено, что наиболее распространенной эмоциональной реакцией жертв является гнев, а психологическими последствиями киберзапугивания -стресс, депрессия и чувство одиночества. Аналогичные результаты были получены на финской [15], австралийской [16], южнокорейской [10], североамериканской [9] выборках.…”
unclassified